Soil Organic Carbon Fractions and Enzymes Activities as Affected by Organic and Inorganic Amendments in an Acid Soil of Meghalaya - Manoj Kumar, S. Hazarika, Ramesh T., L.J. Bordoloi, P. Moirangthem; D. Bhuyan, B.C. Verma, B.U. Choudhury (Journal of the Indian Society of Soil Science, 2017)
Soil organic carbon (SOC) and its fractions (labile and non-labile) are important for sustainability of any agricultural production system as they govern most of the soil properties, and hence soil quality and health. Being a food source for soil microorganisms, they also affect microbial activity, diversity and enzymes activities. The present paper reports the results from a three years (2011-14) field experiment to elucidate the effect of soil amendments (lime and FYM) on SOC fractions and enzymes activity. Results revealed that integrated soil management comprising 50% NPK+FYM @ 5 t ha-1+Lime @ 0.5 t ha-1 significantly improved the SOC fractions, and the proportional changes were more in the labile SOC fractions. Soil enzymes activities were also better correlated with the labile SOC fractions. Rhizosphere soil had proportionally more amount of labile organic carbon (LBC) over total organic carbon (TOC), and also had better enzymatic activities than non-rhizosphere soil. This experiment shows that proper combination of soil amendments improves the SOC fractions, and changes would be more readily reflected by the labile SOC fractions. Soil enzymes activity, which is directly related with the labile SOC fractions, is a good indicator of changes induced by various management practices. Relative changes in the SOC fractions and soil enzymes activity are more pronounced in the rhizosphere than in non-rhizosphere soil.